2014
DOI: 10.5539/ass.v10n21p35
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Teaching Methods that Influence the Acquisition of Practical Skills

Abstract: This study is designed to identify the teaching methods that influence the acquisition of practical skills of mechanical engineering trades students at technical college level using regression analysis. Descriptive survey research design was utilized in carrying out the study. Ninety nine (99) mechanical engineering trades' teachers and fourty six (46) administrators in the technical colleges in north central states of Nigeria responded to a structured questionnaire which addressed the research question. Cronb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…As a result, textile graduates were not effectively equipped with practical skills to modernise the indigenous textile industry. The present finding concur to Audu (2014) who published that graduates from skill training institutions lack skills needed to transform indigenous industries because the pedagogical content knowledge of teachers in technical and vocational training institutions have not succeeded in imparting constructively on practical skills achievement of the graduates. The finding is also in support of Idris & Rajuddin, (2012) who opine that industrial employers have constantly express their worry about the quality of the current technical and vocational graduates not having appropriate skills required for employment in the industries.…”
Section: Discussionsupporting
confidence: 89%
“…As a result, textile graduates were not effectively equipped with practical skills to modernise the indigenous textile industry. The present finding concur to Audu (2014) who published that graduates from skill training institutions lack skills needed to transform indigenous industries because the pedagogical content knowledge of teachers in technical and vocational training institutions have not succeeded in imparting constructively on practical skills achievement of the graduates. The finding is also in support of Idris & Rajuddin, (2012) who opine that industrial employers have constantly express their worry about the quality of the current technical and vocational graduates not having appropriate skills required for employment in the industries.…”
Section: Discussionsupporting
confidence: 89%
“…Researchers like [25] and [26] also indicated that another important aspect for consideration is the teaching and evaluation strategies for the integrated curriculum. Teaching strategies may include the following; (a) Practical project method (b) Workshop method (c) Exploration or Discovery method (d) Demonstration method (e) Field trip method (f) Simulation or Role play method (g) Case study approach (h) Career talk or Resource person's presentation (i) Question and answer (Socratic) method (j) Discussion method, and (k) Lecture method.…”
Section: Entrepreneurship Skillsmentioning
confidence: 99%
“…"SPM" mode advocate that the teacher create free, open chances and space; the students construct their cognitive structure autonomously, obtain the situational feelings, cultivate their interest in independent thinking and develop their understanding [3]. As a major connected closely with the market and reality, financial management major is supposed to practise the linkage of "sound, picture and motion" in aspects from curriculum design, analogue simulation to professional practice and integrated practical training [4].…”
Section: Cultivate Students' Constructive Learning Abilitymentioning
confidence: 99%